1997
DOI: 10.1017/s0031182097001558
|View full text |Cite
|
Sign up to set email alerts
|

Human Toxocara infection of the central nervous system and neurological disorders: a case-control study

Abstract: Infection with Toxocara canis is a common world-wide human helminthiasis, which rarely elicits central nervous system (CNS) impairment. A case-control study to investigate this discrepancy was carried out, in which the cases were 27 adult neurological inpatients for whom a definite aetiological diagnosis was lacking, and for whom positive immunodiagnosis of toxocariasis had been obtained, both in cerebrospinal fluid (CSF) and in serum. Two control groups were used. Controls were adult inpatients with other neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 21 publications
1
48
0
4
Order By: Relevance
“…These results are interesting, not only because of the implications they may carry for the animal's survival in the wild, but also because of the wider implications with respect to human infection. Evidence for cerebral toxocariasis in humans is patchy but there are some indications that larval involvement in the human brain may have some subtle public health implications (Hill, Denham and Scholtz, 1985 ;Marmor et al 1987 ;Magnaval et al 1997). The clinical significance of cerebral infection remains unclear, however, since there are usually other factors involved when the patient presents -such as epilepsy, dementia, and mental retardation (Kaplan et al 2004 ;Magnaval et al 1997 ;Glickman et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…These results are interesting, not only because of the implications they may carry for the animal's survival in the wild, but also because of the wider implications with respect to human infection. Evidence for cerebral toxocariasis in humans is patchy but there are some indications that larval involvement in the human brain may have some subtle public health implications (Hill, Denham and Scholtz, 1985 ;Marmor et al 1987 ;Magnaval et al 1997). The clinical significance of cerebral infection remains unclear, however, since there are usually other factors involved when the patient presents -such as epilepsy, dementia, and mental retardation (Kaplan et al 2004 ;Magnaval et al 1997 ;Glickman et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…foram identificados em apenas uma amostra de cenoura orgânica. A ocorrência desse helminto nas hortaliças pode ser proveniente de solos contaminados com ovos do parasita originário de cães ou gatos parasitados, ou devido ao comprometimento do sistema de irrigação (MAGNAVAL et al, 1997).…”
Section: Avaliação Parasitológicaunclassified
“…In a case control study Magnaval et al 22 demonstrated that Toxocara infection is not associated with a recognizable neurological syndrome, although several cases had a positive Western blot for both cerebrospinal fluid and serum. However a significant association between seizures and positive serology for Toxocara has been reported in Italy 1 and in Bolivia 29 .…”
mentioning
confidence: 99%